The current use and potential of cost benefit analysis in water sector projects - Dino Ratnaweera (IWA Publishing, 2021)
The investment needed in global water infrastructure is significant. Infrastructures in water supply and sanitation alone are expected to require USD 6.7 trillion by 2050. These infrastructures must provide investment justifications when seeking funding from disbursement sources, in competition with other services (such as health, education, transport, elderly care etc.). We present a review that identifies monetary valuation gaps in regional and global cost benefit analysis (CBA) guidelines that underpin investment justifications. Case studies of Scandinavian appraisal reports written according to these guidelines indicate an alarmingly low use of monetary valuation on socioeconomic and environmental impacts caused by water sector projects. The findings suggest a need for broader and more accessible recommendations for water sector specific valuation methods. The need to develop a more accessible CBA framework for water infrastructure project managers is theoretically discussed, with emphasis on utilising monetary valuation methods and secondary source data. We identify valuation methods fragmentally discussed in the guidelines that should be adapted and applied, in time and cost-efficient ways, to water infrastructure projects. HIGHLIGHTS Scandinavian water sector CBA appraisals lack monetary valuation of socioeconomic and environmental impacts of water infrastructure projects.; Our study of 15 CBA guidelines reveal fragmented and conservative valuation practices, possibly causing the low CBA practice rate in the water sector.; Secondary data sources can be used as quantitative components in a more accessible and applicable CBA.;